Genotypic differences for salt tolerance in bael (Aegle marmelos) cultivars - SINGH, ANSHUMAN; SHARMA, PARBODH C; KUMAR, ASHWANI; MEENA, M D; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2023)
Salinity induced changes in physiological relations and the concomitant effects on plant growth were recorded in four bael (Aegle marmelos Correa) cultivars, viz. NB-5, NB-9, CB-1 and CB-2. Plants raised in normal soil (ECe 1.3 dS/m) were irrigated with tap (ECiw 0.5 dS/m) and saline (ECiw 3 and 6 dS/m) waters. Data were recorded for growth, physiological parameters and mineral nutrition 180 days after imposing the salt treatments. NB-5 outperformed other cultivars under saline conditions by maintaining higher leaf chlorophyll and proline levels, retaining Na+ ions in stem and root tissues and by preferentially accumulating K+ and Ca2+ ions to overcome the toxic effects of Na+. Break down of salt tolerance in other cultivars at 6 dS/m salinity can be explained by build up of Na+ to the toxic levels and an accompanying decrease in leaf and stem K+ concentrations. Based on these findings, bael cultivar NB-5 appears to be suitable for commercial cultivation in salt-affected soils.